2004
DOI: 10.1021/ac0352575
|View full text |Cite
|
Sign up to set email alerts
|

Interdigitated Array Microelectrode-Based Electrochemical Impedance Immunosensor for Detection of Escherichia coli O157:H7

Abstract: A label-free electrochemical impedance immunosensor for rapid detection of Escherichia coli O157:H7 was developed by immobilizing anti-E. coli antibodies onto an indium-tin oxide interdigitated array (IDA) microelectrode. Based on the general electronic equivalent model of an electrochemical cell and the behavior of the IDA microelectrode, an equivalent circuit, consisting of an ohmic resistor of the electrolyte between two electrodes and a double layer capacitor, an electron-transfer resistor, and a Warburg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
228
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(235 citation statements)
references
References 32 publications
4
228
0
3
Order By: Relevance
“…In general, the technique has been applied to detecting and/or quantifying food-borne microorganisms [1]. Recently, it has received attention from researchers in other fields due to its ability of rapid measurement for bacterial concentrations [4][5][6][7]. In some studies, the dielectrophoretic impedance measurement method was combined with antigen-antibody reaction [6,8,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the technique has been applied to detecting and/or quantifying food-borne microorganisms [1]. Recently, it has received attention from researchers in other fields due to its ability of rapid measurement for bacterial concentrations [4][5][6][7]. In some studies, the dielectrophoretic impedance measurement method was combined with antigen-antibody reaction [6,8,9].…”
mentioning
confidence: 99%
“…Recently, it has received attention from researchers in other fields due to its ability of rapid measurement for bacterial concentrations [4][5][6][7]. In some studies, the dielectrophoretic impedance measurement method was combined with antigen-antibody reaction [6,8,9]. In other studies, the electrical impedance measurements were used to detect the ionic metabolites produced during the bacterial growth [10,11].…”
mentioning
confidence: 99%
“…The integration of impedance technique with biosensor technology has led to the recent development of impedance biosensors that is expending rapidly for bacteria detection (Ruan et al, 2002;Yang et al, 2004b;Radke and Alocilja 2005). Impedance biosensors for bacteria detection are based on impedance analysis of the electrical properties of bacterial cells when they are attached to or associated with the electrodes.…”
Section: Role Of Impedance Techniques For Bacteria Detectionmentioning
confidence: 99%
“…For example, micrometer IDA electrodes are suitable for sensing of biological cells, while nanometer IDAs are more proper for sensing DNA. Yang et al (2004b) reported a label-free electrochemical impedance immunosensors for detection of E. coli O157:H7 using interdigitated microelectrodes. The IDA consisted of a pair of microband array indium-tin oxide (ITO) electrodes.…”
Section: Electrochemical Impedance Biosensors Using Redox Probesmentioning
confidence: 99%
“…Yang et al described a label-free impedance immunosensor for the rapid detection of Escherichia coli O157:H7 by immobilizing anti-E. coli antibodies onto an indium-tin oxide interdigitated array (IDA) microelectrode. 162 The authors showed that the immobilization of antibodies and the binding of E. Coli cells to the IDA microelectrode surface increased the electron-transfer resistance, which was directly measured with electrochemical impedance spectroscopy in the presence of [Fe(CN)6]3-/4-as a redox probe. The electron-transfer resistance was correlated with the concentration of E. Coli cells in a range from 10 5 to 10 8 cfu/mL with the detection limit of 10 6 cfu/mL which was comparable with other label free electrochemical immunoassays.…”
Section: Other Immunosensorsmentioning
confidence: 99%